KEMAMPUAN RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PADA BANK-BANK BADAN USAHA MILIK NEGARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agri Kurniasari; Dyah Fitriani (Universitas Ahmad Dahlan, 2013)
This Research purposed to analyze any influence of Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return on Equity (ROE), and BOPO Ratio toward Earning Changes at State Owned Bank registered in Indonesia Stock Exchange (IDX) during 2008-2012. The population in this research are all of State Owned Bank registered on Indonesian Stock Exchange (IDX) during 2008-2012, and the samples in this research are all of populations. They are Bank Mandiri (Persero) Tbk, Bank Negara Indonesia (Persero) Tbk, Bank Rakyat Indonesia (persero) Tbk, and Bank Tabungan Negara (Persero) Tbk. The data can be found from quartely financial statements publicated on Indonesia banking directory and processed using panel data processing and partial (t) test. The result of this research showed that Loan to Deposit Ratio (LDR) partialy not significance influental toward Earning Changes. Significancy value 0.5003 more than alpha 5%. Capital Adequacy Ratio (CAR) partialy not significance influental toward Earning Changes. Significancy value 0.8248 more than alpha 5%. Return on Equity (ROE) partialy not significance influental toward Earning Changes. Significancy value 0.0784 more than alpha 5%. BOPO Ratio partialy not significance influental toward Earning Changes. Significancy value 0.6577 more than alpha 5%